2019
DOI: 10.14744/alrj.2019.28290
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Language Learning Strategies and Achievement among EFL University Students

Abstract: This study investigated the relationship between language learning strategies and achievement among Yemeni EFL university students. It also identified the differences between high and low achievers in using language learning strategies. Seventy students were randomly selected from the fourth level on the basis of their university scores as high and low achievers. The study adopted the SILL questionnaire developed by Oxford (1990) to collect the data of the study. The obtained data were statistically analyzed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Regarding the research designs identified, 34 investigations covered in this literature review can be considered non-intervention research. In this respect, 22 correlational studies attempted to associate LLS and other variables, such as learning characteristics [16], language proficiency [17], [18], [21], [27], [28], [41], [56], self-efficacy [19], [50], [53], self-regulation [23], [24], language learning beliefs [25], personality traits [29], learning styles [31], among others. Moreover, a total of 12 investigations can be categorized as survey research for they emphasize depicting the participants' use of LLS (e.g., [26], [30], [33], [35], [36], [40], [44], [48]).…”
Section: Methodology Of Research On Lls In Efl Contextsmentioning
confidence: 99%
“…Regarding the research designs identified, 34 investigations covered in this literature review can be considered non-intervention research. In this respect, 22 correlational studies attempted to associate LLS and other variables, such as learning characteristics [16], language proficiency [17], [18], [21], [27], [28], [41], [56], self-efficacy [19], [50], [53], self-regulation [23], [24], language learning beliefs [25], personality traits [29], learning styles [31], among others. Moreover, a total of 12 investigations can be categorized as survey research for they emphasize depicting the participants' use of LLS (e.g., [26], [30], [33], [35], [36], [40], [44], [48]).…”
Section: Methodology Of Research On Lls In Efl Contextsmentioning
confidence: 99%
“…Many studies have confirmed that the poor level of academic achievement in English is due to the use of the traditional method and the failure to make the learner the centre of the educational process (Khaleel & Alrefaee, 2018). Searching for an effective method of teaching still occupies the minds of researchers.…”
Section: Introductionmentioning
confidence: 99%